# How do you solve #4( a - 1) = 7a + 2#?

##### 2 Answers

Apr 21, 2018

#### Explanation:

To get to those follow these steps:

- Expand the brackets, so
#4(a-1)# becomes#4a-4# - Rearrange so you have the variables on the same side
#-> -4 -2 = 7a-4a# (change signs when moving across the equals sign) - Simplify
#-> -6 = 3a# - Divide both sides by
#3# so#a# is by itself#-> -6/3=a# #-6/3 = -2# , therefore,#a# must equal#-2#

Apr 21, 2018

a = -2

#### Explanation:

On the left hand side, multiply each term inside the brackets by 4

Subtract 2 from both sides

Subtract 4a from both sides

Divide both sides by 3